KUBERNETES: THE CORNERSTONE OF ENTERPRISE PLATFORM ENGINEERING - Hari Yerramsetty (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article explores the transformative role of Kubernetes in enterprise platform engineering, highlighting its emergence as a cornerstone technology for modern IT infrastructures. As organizations increasingly adopt microservices architectures and cloud-native practices, Kubernetes offers a comprehensive solution for deploying, managing, and scaling containerized applications across diverse environments. The article examines key features driving Kubernetes adoption, including advanced container orchestration, dynamic scalability, high availability, infrastructure abstraction, and declarative configuration. It also delves into the significant impacts of Kubernetes on enterprise IT, such as streamlined development and deployment processes, optimized resource management, simplified operations, enhanced security and compliance, and extensive ecosystem integration. Through an analysis of adoption trends, feature utilization, and real-world examples, the article demonstrates how Kubernetes addresses critical software development and operations challenges, ultimately enabling organizations to innovate faster, reduce costs, and maintain competitive edge in the digital landscape.